Seasonal variation of organochlorine pesticides in the gaseous phase and aerosols over the East China Sea. (May 2015) - Ji, Tianyi; Lin, Tian; Wang, Fengwen; Li, Yuanyuan; Guo, Zhigang
Abstract: Eighty paired gaseous phase and PM2.5 (particulate matter < 2.5 μm in diameter) samples, covering four seasons from October 2011 to August 2012 were collected simultaneously from a remote island in the East China Sea (ECS). The samples were analyzed for organochlorine pesticides (OCPs) to determine their seasonal variation and potential sources over the coastal marine environment. The concentrations of individual OCPs in the PM2.5 samples were higher in winter and lower in summer, and the reverse trend was observed for the measured OCP compounds (except hexachlorocyclohexanes, HCHs) in the gaseous phase. Principal component analysis revealed one trend that contributed 40% to PM2.5-bound OCPs characterized by β-HCH, α-HCH, p, p ′-dichlorodiphenyldichloroethane ( p, p ′-DDD), p, p ′-dichlorodiphenyldichloroethylene ( p, p ′-DDE), and chlordanes; whereas two seasonal trends, represented by dichlorodiphenyltrichloroethanes (DDTs) or chlordanes and HCHs, were responsible for 38% and 23% of the gaseous OCPs, respectively. Continental outflow driven by the East Asian monsoon brought large quantities of particulate OCPs to the ECS, especially in winter. Possible fresh sources or net volatilization from the Yangtze River induced by both higher ambient temperature and higher discharge rates caused the higher gaseous DDT and chlordane levels observed in summer. However, the lower concentrations of gaseous HCHs observed in summer suggested that net volatilization had a relatively limited impact on gaseous HCHs due to the long-term prohibition of their use and their low residual levels in the catchment, whereas the elevated concentrations of gaseous HCHs in winter controlled by gas–particle partitioning, resulted from increased particulate HCHs producing a partial shift to gaseous HCHs over ECS. Highlights: 80 paired gaseous phase and PM2.5 samples were collected for OCP analysis in the ECS. Higher particulate OCPs were observed in winter due to the continental outflow. The inconsistent pattern of the individual OCPs in the gaseous phase was observed. There was a short-term application of DDTs and Chlordanes in the upwind areas.